Novel approaches to quantify CNS involvement in children with Pompe disease. (11th August 2020) - Korlimarla, Aditi; Spiridigliozzi, Gail A.; Crisp, Kelly; Herbert, Mrudu; Chen, Steven; Malinzak, Michael; Stefanescu, Mihaela; Austin, Stephanie L.; Cope, Heidi; Zimmerman, Kanecia; Jones, Harrison; Provenzale, James M.; et al.
Abstract : Objective: To characterize the extent of CNS involvement in children with Pompe disease using brain MRI and developmental assessments. Methods: The study included 14 children (ages 6–18 years) with infantile Pompe disease (IPD) (n = 12) or late-onset Pompe disease (LOPD) (n = 2) receiving enzyme replacement therapy. White matter (WM) hyperintense foci seen in the brain MRIs were systematically quantified using the Fazekas scale (FS) grading system with a novel approach: the individual FS scores from 10 anatomical areas were summed to yield a total FS score (range absent [0] to severe [30]) for each child. The FS scores were compared to developmental assessments of cognition and language obtained during the same time period. Results: Mild to severe WM hyperintense foci were seen in 10/12 children with IPD (median age 10.6 years) with total FS scores ranging from 2 to 23. Periventricular, subcortical, and deep WM were involved. WM hyperintense foci were seen throughout the path of the corticospinal tracts in the brain in children with IPD. Two children with IPD had no WM hyperintense foci. Children with IPD had relative weaknesses in processing speed, fluid reasoning, visual perception, and receptive vocabulary. The 2 children with LOPD had no WM hyperintense foci, and high scores on most developmental assessments. Conclusion: This study systematically characterized WM hyperintense foci in children with IPD, which could serve as a benchmark for longitudinal follow-up of WM abnormalities in patients with Pompe disease and other known neurodegenerative disorders or leukodystrophies in children.